Frequency of Antenatal Depression in Obstetric Patients Attending Antenatal Clinic: Department of Obstetrics and Gynaecology, Hayatabad Medical Complex, Peshawar, Pakistan - Sabeena, Abida; Nageen, Kainat; Bibi, Lubna; Baz, Komal; Shamsher, Saadia; Arshad, Sanniya (Pakistan Journal of Health Sciences, 2026)
Antenatal depression is a prevalent but poorly understood mental health disorder with adverse maternal and fetal outcomes. It is common in different populations, with its risk factors being different, especially among the low- and mid-income countries. Timely intervention requires early diagnosis. Objectives: To identify the prevalence of antenatal depression and the related sociodemographic and obstetric variables in women visiting the antenatal clinic. Methods: The study was cross-sectional and conducted between January 1, 2025, and July 30, 2025, among 278 pregnant women through consecutive sampling. The Edinburgh Postnatal Depression Scale (EPDS) was used to measure antenatal depression, and a cutoff score of ≥13 was considered to be depressed. The analysis was performed with SPSS version 25.0, and descriptive statistics, a bivariate analysis, and binary logistic regression were applied to determine independent predictors (p ≤ 0.05 was taken to be significant). Results: Antenatal depression was found to be prevalent (27.3, 95% CI: 21.9-32.7%). Major independent predictors were low socioeconomic status (AOR = 2.41; p=0.002), unplanned pregnancy (AOR = 1.94; p = 0.023) and past adverse obstetric outcomes (AOR=1.72; p=0.048). Conclusions: Depression occurred in more than a quarter of antenatal women in this tertiary care facility. The key risk factors are socioeconomic disadvantage, unintended pregnancy, and poor obstetric history. It is advised to conduct regular mental health screening and targeted interventions throughout the antenatal care to enhance maternal and fetal outcomes.